Implementasi Honor Amil Zakat Perspektif Fatwa MUI Nomor 8 Tahun 2011 Tentang Amil Zakat : Studi Kasus LAZ Masjid Raya Bintaro Jaya - Siagian, Fatimah; Rajuli, Achmad Dzikri; Khoirunnisa (Tasfiyah : Journal of Islamic Law and Sharia Economics, 2026)
The honorarium for zakat administrators (amil) plays a vital role in ensuring professional and accountable zakat institution management. This study examines the case of the Zakat Management Institution at Masjid Raya Bintaro Jaya (LAZ MRBJ), focusing on how honoraria are distributed to amil and assessing its alignment with the Indonesian Council of Ulama (MUI) Fatwa No. 8 of 2011. This fatwa provides guidelines regarding the legality, proportion, and principles of zakat fund utilization for amil operations in accordance with sharia. The research employs a qualitative descriptive method using an empirical legal approach. Data were collected through in-depth interviews, observations, and documentation of LAZ MRBJ's honorarium policies and practices. This approach allows for a comprehensive understanding of practical implementation while evaluating it against Islamic legal norms and applicable regulations. Findings reveal that LAZ MRBJ's honorarium implementation reflects professionalism, efficiency, accountability, and institutional independence. The system complies with MUI Fatwa No. 8/2011 in terms of amil legality, honorarium proportion, and reporting mechanisms. Moreover, initiatives such as amil training and the development of productive waqf—though not explicitly mentioned in the fatwa remain within sharia boundaries and support sustainable and transparent zakat management.